2017
DOI: 10.3390/su9122328
|View full text |Cite
|
Sign up to set email alerts
|

Household Energy Consumption Behaviour for Different Demographic Regions in Thailand from 2000 to 2010

Abstract: Abstract:Since 1995, the residential sector has been a fast-growing energy consumption sector in Thailand. This sector contributes dramatically to the growth of Thailand's electricity and oil demand. Our study analysed Thailand's residential energy consumption characteristics and the seven underlying factors affecting the growth in energy use of five demographic regions using an energy input-output method. Embodied energy decomposition revealed that direct energy consumption accounted for approximately 30% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…L = (I -A) -1 , the n × n Leontief inverse matrix, accounts for not only the direct production effects through the domestic intermediate coefficients, but also all the indirect production effects in the whole economic process [19,23]. Based on the Input-output theory [24], energy and economy can be modelled by applying the SDA method and combining with energy indicator, as follows [5,25,[66][67][68][69][70][71]…”
Section: Constructing the Sda Methodsmentioning
confidence: 99%
“…L = (I -A) -1 , the n × n Leontief inverse matrix, accounts for not only the direct production effects through the domestic intermediate coefficients, but also all the indirect production effects in the whole economic process [19,23]. Based on the Input-output theory [24], energy and economy can be modelled by applying the SDA method and combining with energy indicator, as follows [5,25,[66][67][68][69][70][71]…”
Section: Constructing the Sda Methodsmentioning
confidence: 99%
“…In Thailand, energy consumption in the household sector both in rural and urban areas has been growing rapidly since 1995. Growth in residential energy consumption in the northern, northeastern, and southern regions has been strongly driven by changes in per capita income [20]. In a survey of energy use in northern Thailand and metropolitan Bangkok, Chiang Mai University [21] found that the average electricity consumption per household in rural areas and urban areas was 870 and 1467 kWh, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The use of energy-efficient products is an important way of restraining the household energy demand. However, the market prices of energy-efficient products, such as five-star-rated energy-saving air conditioners, tend to be higher than those of regular products [9,10].…”
Section: Introductionmentioning
confidence: 99%